A clinical study of physiological cutaneous manifestations in early neonates at a tertiary care center in western Rajasthan - Paras Choudhary; Rajesh Datt Mehta; Bhikam Chand Ghiya; Divya Sharma (Wolters Kluwer Medknow Publications, 2022)
Introduction: The rapidly adapting neonatal skin, being anatomically and physiologically distinct from an adult, may exhibit a variety of entities, ranging from mild self-limiting to the severe life-threatening ones. The transition of neonatal skin from an aqueous to an air-dominant environment results in various changes, both physiological and pathological. Physiological and pathological dermatoses should be differentiated to avoid unnecessary treatment and psychological distress to parents. The present study was carried out to determine prevalence and patterns of physiological cutaneous manifestations among early neonates in western Rajasthan. Materials and Methods: This hospital-based, descriptive, observational study was carried at a tertiary care hospital over a period of 1 year. After due informed consent, total of 5000 early neonates delivered during this time were included in the study. A detailed history was taken and dermatological examination of each neonate was carried out. Laboratory procedures were performed to confirm diagnosis if required. Data were collected in a predesigned pro forma. Results: Out of 5000 newborns, 64.96% were male and 35.04% female. Ninety-two percentage had physiological changes and 21% had pathological changes. The physiological skin changes observed in order of frequency were sebaceous hyperplasia (65.32%), milia (51.12%), physiological desquamation (41.02%), vernix (35%), and physiological jaundice (9.32%). Cutis marmorata, harlequin skin changes, and lanugo hair were seen more in low-birth weight and preterm neonates. Conclusion: Most of the early neonatal dermatoses are physiological and transient in nature. Hence, it is important to identify and differentiate them from other serious conditions, thereby avoiding unnecessary diagnostic and therapeutic procedures and provide reassurance to overenthusiastic dermatologists, pediatricians, and parents.